Strategic Assets Explore The Influence of Human Capital, Organizations, and Relationships For Performance Excellence: (Case Study of Cimahi City Bappenda) - Riadi, Farid; Coenraad, Dhea Perdana (Pascasarjana Universitas Pasundan, 2024)
Human resource management (HR) and organizational performance are the focus of this research in the context of government sector management in Indonesia. This study aims to identify and analyze the influence of human resource capital, organizational capital and relationship capital on performance. The research method used is quantitative research with path analysis techniques. The results of the analysis show that the three independent variables have a significant influence on employee performance, with a total contribution of 87.80%. Human resource capital has the most dominant impact, followed by organizational capital and relationship capital. Even though relationship capital has a significant impact, it still requires support from high levels of human resource capital and organizational capital. The implication of this research is the importance of human resource management in achieving the success of government organizations in the future, with a focus on the management of the State Civil Apparatus (ASN) and the challenges faced such as violations of discipline and abuse of authority. In addition, this research also highlights the importance of organizational capital and relationship capital in improving overall organizational performance and building mutually beneficial relationships with stakeholders. With a deep understanding of the complexity of the relationships between the variables studied, this research provides important insights for decision makers in designing human resource management strategies and managing stakeholder relationships to achieve organizational success in the future.